Evidence for sensitized fatigue pathways in patients with chronic fatigue syndrome. Issue 4 (April 2015) - Staud, Roland; Mokthech, Meriem; Price, Donald D.; Robinson, Michael E.
Abstract : Abstract: Patients with chronic fatigue syndrome (CFS) frequently demonstrate intolerance to physical exertion that is often reported as increased and long-lasting fatigue. Because no specific metabolic alterations have been identified in CFS patients, we hypothesized that sensitized fatigue pathways become activated during exercise corresponding with increased fatigue. After exhausting handgrip exercise, muscle metabolites were trapped in the forearm tissues of 39 CFS patients and 29 normal control (NC) by sudden occlusion for up to 5 minutes. A nonocclusive condition of similar duration was used as control. Repeated fatigue and pain ratings were obtained before and after exercise. Mechanical and heat hyperalgesia were assessed by quantitative sensory testing. All subjects fulfilled the 1994 Fukuda Criteria for CFS. Normal control and CFS subjects exercised for 6.6 (2.4) and 7.0 (2.7) minutes ( P > 0.05). Forearm occlusion lasted for 4.7 (1.3) and 4.9 (1.8) minutes in NC and CFS subjects, respectively ( P > 0.05). Although fatigue ratings of CFS subjects increased from 4.8 (2.0) to 5.6 (2.1) visual analogue scale (VAS) units during forearm occlusion, they decreased from 5.0 (1.8) to 4.8 (2.0) VAS units during the control condition without occlusion ( P = 0.04). A similar time course of fatigue ratings was observed in NC ( P > 0.05), although their ratings were significantly lower than those of CFS subjects ( P < 0.001). Quantitative sensory testing demonstrated heat and mechanical hyperalgesia in CFS subjects. Our findings provide indirect evidence for significant contributions of peripheral tissues to the increased exercise-related fatigue in CFS patients consistent with sensitization of fatigue pathways. Future interventions that reduce sensitization of fatigue pathways in CFS patients may be of therapeutic benefit. Abstract : Trapping of muscle metabolites in forearm tissues worsens overall fatigue of CFS patients more than that of NC suggesting sensitized fatigue pathways in CFS.